A poly(vinyl alcohol)/poly(stearyl acrylate) core‐shell fibers with robust performance realized by taking advantages of the phase change property. Issue 11 (18th October 2021) - Qu, Meijie; Wang, Hai; Zheng, Nan; Chen, Qiushan; Tang, Ping; Bin, Yuezhen
Abstract: A phase change fiber with long‐term stability, temperature dependent transparency and melt‐healing properties were prepared using polyvinyl alcohol (PVA) as the shell layer and polystearyl acrylate (PSA) lightly crosslinked by ethoxylated trimethylolpropane triacrylate (ETPTA) as the core layer. It was found the PVA/P(SA‐ETPTA) core‐shell fiber exhibited a melt enthalpy of 43 J/g (coagulation bath temperature −15 °C, core layer diameter 0.2 mm, spinning rate 1.0 mm/s) and an extremely high stability after 100 heating–cooling cycles. The as‐spun core‐shell fiber was fragile, but the flexibility was greatly improved after it was drawn to 800% of the original length. The PVA shell forming tunneling for the P(SA‐ETPTA) core layer, which could heal after fracture on condition of PSA melting. The melting and crystallization of PSA side chains enabled a temperature dependent light transmittance of the PVA/P(SA‐ETPTA) fibers, which was ascribed to the phase separation between PSA and PETPTA around the melting point of the PSA composition. As a whole, the core‐shell fibers showed robust performance as a phase change fiber. Further aggregate structure and orientation structure investigation on the PVA/P(SA‐ETPTA) fiber was detected by wide angle X‐ray diffraction and small angle X‐ray scattering. Abstract : A PVA/P(SA‐ETPTA) core shell fiber showed temperature dependent transparency change ascribed to the phase separation of PSA and PETPTA phases which were in crystalline and amorphous states, respectively at room temperature, but became amorphous at the temperature higher than 50 ℃.